Parental mental health and risk of poor mental health and death by suicide in offspring: a population-wide data-linkage study - O'Reilly, Dermot; Maguire, Aideen (International Journal of Population Data Science, 2018)
Introduction Suicide is a major public health concern and identifying those most at risk is vital to ensure the implementation of effective interventions. There are known associations between parental and sibling mental health but little is known on the effect of parental mental on a child’s risk of death by suicide. Objectives and Approach This population-wide data linkage study utilised data from the 2011 Northern Ireland Census linked to 5 years’ death records (2011-2015) to construct multi-level regression models to determine if children living with parents with poor self-rated mental health are at an increased risk of poor mental health themselves and whether they are at an increased risk of death by suicide. Results Of the 618,970 individuals who live with their parents, 13.7% live with parents with poor mental health, 11.6% have poor mental health themselves and 0.1% (n=225) died by suicide. Living with a parent with poor mental health was associated with likelihood of poor mental health in children. After adjustment for age, gender, physical illness, socio-economic status and own mental health status, children with 1 parent with poor mental health were 67% more likely to die by suicide compared to children of parents with good mental health (OR=1.67, 95%CI 1.19, 2.33). The effect size increases for children living with 2 parents with poor mental health. Conclusion/Implications Parental mental health is associated with a child’s suicide risk even after adjustment for their own mental health status. This is an at-risk group.